Total Attenuation Cross-Sections of Several Proteins at 661.6, 1173 and 1332.5 keV - P. Pawar, Pravina; P. Tadkalkar, Alka; K. Bichile, Govind (Asian Journal of Chemistry, 2012)
Total attenuation cross sections of several proteins have been measured for 661.6, 1173 and 1332.5 keV photons by empirical formula s = 2.2 A E-0.43. The values are compared with the values calculated with the aid of mixture rule from the data of Hubbell for the individual elements.